Свято в Полтаві - Лисенко, О. (Народна творчість та етнографія, 2005)
The article is dedicated to the 120th anniversary of Ostap Lysenko, the great Ukrainian musicologist, a choral conducter, a pedagogue and a public figure, M. Lysenko's son. The author reconstructs his portrait as a master and a public figure. O. Lysenko's autobiography, the recollections of his colleagues and pupils are given as well. A chapter from the book by O. Lysenko "Festivities in Poltava" about the building of Kotlyarevskyj monument is also published.